Method for producing silica particles, method for producing silica sol, polishing method, method for producing semiconductor wafer, and method for producing semiconductor device

By controlling water concentration in the reaction system to 3% by mass, the method suppresses the formation of fine particles, improving polishing efficiency and accuracy by ensuring effective adhesion and removal of silica particles.

JP7622444B2Active Publication Date: 2025-01-28MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2021005174
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-15
Publication Date
2025-01-28
Estimated Expiration
2041-01-15

AI Technical Summary

Technical Problem

Existing methods for producing silica particles through hydrolysis and condensation reactions often result in the generation of fine particles, which adhere to polishing bodies during polishing and are difficult to remove, affecting polishing efficiency and quality.

Method used

Control the concentration of water in the reaction system from the start to the end of the hydrolysis and condensation reactions within 3% by mass, maintaining the solubility of tetraalkoxysilane and suppressing the formation of fine particles.

Benefits of technology

The method effectively reduces the generation of fine particles, enhancing polishing performance by improving the adhesion and removal of silica particles, thereby improving the accuracy and efficiency of polishing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622444000001
    Figure 0007622444000001
Patent Text Reader

Abstract

To provide a method for producing silica particles that prevents the occurrence of fine particles.SOLUTION: A method for producing silica particles includes subjecting tetraalkoxysilane to hydrolysis reaction and condensation reaction, in which, from the start to end of the hydrolysis reaction and the condensation reaction, changes in the concentration of water within the reaction system are controlled within 3 mass%. There are also provided: a polishing method that performs polishing with a polishing composition containing a silica sol obtained by the silica sol production method; a method for producing a semiconductor wafer, including the polishing method; and a method for producing a semiconductor device, including the polishing method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing silica particles, a method for producing a silica sol, a polishing method, a method for producing a semiconductor wafer, and a method for producing a semiconductor device. [Background technology]

[0002] Polishing methods using polishing liquids are known as methods for polishing the surfaces of materials such as metals and inorganic compounds. In particular, in the final polishing of prime silicon wafers for semiconductors and reclaimed silicon wafers, and in chemical mechanical polishing (CMP) for planarizing interlayer insulating films during semiconductor device manufacturing, forming metal plugs, forming buried wiring, and the like, the surface condition has a significant effect on the semiconductor characteristics, so the surfaces and end faces of these components are required to be polished with extremely high precision.

[0003] In such precision polishing, a polishing composition containing silica particles is adopted, and colloidal silica is widely used as the abrasive grains, which are the main component. Depending on the manufacturing method, colloidal silica is known to be produced by pyrolysis of silicon tetrachloride (fumed silica, etc.), by deionization of alkali silicate such as water glass, and by hydrolysis and condensation reaction of alkoxysilane (generally called the "sol-gel method").

[0004] Many studies have been conducted on methods for producing silica particles. For example, Patent Document 1 discloses a method for producing silica particles by hydrolysis and condensation reactions of alkoxysilane. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-060217 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, silica particles obtained by hydrolysis and condensation reactions may produce silica particles (hereinafter referred to as fine particles) that are much smaller than the desired particle size, depending on the production conditions. These fine particles have the problem of adversely affecting the polishing process, such as by adhering to the object to be polished during polishing, lowering the polishing rate, or being difficult to remove by cleaning after polishing.

[0007] The method for producing silica particles disclosed in Patent Document 1 has a problem in that the concentration of water in the reaction system of the hydrolysis reaction and condensation reaction changes significantly from the start of the reaction to the end of the reaction, and this may result in the generation of fine particles due to a deterioration in the solubility of tetraalkoxysilane in the reaction solution and silicic acid produced by the hydrolysis reaction.

[0008] The present invention has been made in view of the above problems, and an object of the present invention is to provide a method for producing silica particles which suppresses the generation of fine particles. [Means for solving the problem]

[0009] In the past, suitable manufacturing conditions for obtaining silica particles suppressed in the generation of fine particles have not been disclosed. However, the present inventors have conducted extensive research and found that the generation of fine particles can be suppressed by reducing the change in water concentration in the reaction system of the hydrolysis reaction and the condensation reaction, and have completed the present invention.

[0010] That is, the gist of the present invention is as follows. [1] A method for producing silica particles by subjecting tetraalkoxysilane to a hydrolysis reaction and a condensation reaction, in which the change in water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to a reaction end is kept within 3 mass%. [2] A method for producing silica particles according to [1], comprising adding a solution (B) containing a tetraalkoxysilane and a solution (C) containing water to a solution (A) containing water, and subjecting the tetraalkoxysilane to a hydrolysis reaction and a condensation reaction. [3] The method for producing silica particles according to [1] or [2], wherein the reaction temperatures of the hydrolysis reaction and the condensation reaction are 20°C to 50°C. [4] The method for producing silica particles according to any one of [1] to [3], wherein the water concentration in the reaction system is kept at 20 mass % or less from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction. [5] A method for producing silica particles according to any one of [1] to [4], further comprising the following step (1): Step (1): A step of concentrating the obtained dispersion liquid of silica particles and adding a dispersion medium. [6] The method for producing silica particles according to [5], further comprising the following step (2): Step (2): A step of subjecting the dispersion liquid of silica particles obtained in step (1) to a pressure and heat treatment. [7] A method for producing a silica sol, comprising the method for producing silica particles according to any one of [1] to [6]. [8] The method for producing a silica sol according to [7], wherein the concentration of silica particles in the silica sol is 3% by mass to 50% by mass. [9] A polishing method, comprising the steps of: polishing with a polishing composition containing a silica sol obtained by the method for producing a silica sol according to [7] or [8].

[10] A method for manufacturing a semiconductor wafer, comprising the polishing method described in [9].

[11] A method for manufacturing a semiconductor device, comprising the polishing method described in [9]. Effect of the Invention

[0011] The method for producing silica particles of the present invention can obtain silica particles in which the generation of fine particles is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified and practiced in various ways within the scope of the gist. In addition, when the expression "~" is used in this specification, it is used as an expression including the numerical values ​​or physical property values ​​before and after it.

[0013] (Method of producing silica particles) The method for producing silica particles of the present invention is a method for producing silica particles by subjecting tetraalkoxysilane to hydrolysis and condensation reaction, and is a method for producing silica particles in which the change in water concentration in the reaction system from the start of the hydrolysis and condensation reactions to the end of the reactions is kept within 3 mass %. By keeping the water concentration within 3 mass %, the solubility of tetraalkoxysilane and silicic acid produced by the hydrolysis reaction in the reaction solution is maintained, and the generation of fine particles can be suppressed. Keeping the change in water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to within 3 mass% means that the difference between the maximum water concentration and the minimum water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction is 3 mass% or less.

[0014] The water concentration in the reaction system refers to the total amount of water in the total amount of substances other than tetraalkoxysilane and silica in the reaction system in the hydrolysis reaction and condensation reaction. That is, the concentration of water in the reaction system is the total amount of water in the total amount of solution (A) described below at the start of the reaction, and is the total amount of water in the total amount of substances (water, catalyst, solvent, and substances such as alcohol generated in the reaction system) excluding tetraalkoxysilane and silica generated in the reaction during the reaction.

[0015] The change in water concentration in the reaction system from the start of the hydrolysis reaction and condensation reaction to the end of the reaction is preferably within 2 mass%, and more preferably within 1 mass%, in order to maintain the solubility of the tetraalkoxysilane and the silicic acid produced by the hydrolysis reaction in the reaction solution.

[0016] Since the method for producing silica particles of the present invention has excellent controllability of hydrolysis and condensation reactions, it is preferable to add a solution (B) containing a tetraalkoxysilane and a solution (C) containing water to a solution (A) containing water, and to cause the tetraalkoxysilane to undergo hydrolysis and condensation reactions.

[0017] The solution (A) preferably contains water, since this allows the hydrolysis reaction of the tetraalkoxysilane to proceed.

[0018] The solution (A) preferably contains an alkali catalyst, since this can increase the reaction rates of the hydrolysis reaction and condensation reaction of the tetraalkoxysilane. Examples of the alkali catalyst in the solution (A) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, is easy to control the particle shape, can suppress the inclusion of metal impurities, is highly volatile, and is easy to remove after the hydrolysis reaction and the condensation reaction.

[0019] The solution (A) preferably contains a solvent other than water because this solvent has excellent solubility in the reaction solution of tetraalkoxysilane. Examples of the solvent other than water in the solution (A) include methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These solvents may be used alone or in combination of two or more. Among these solvents, alcohol is preferred, more preferably methanol or ethanol, and even more preferably methanol, because it is easy to dissolve tetraalkoxysilane, the by-product is the same as that used in the hydrolysis reaction and the condensation reaction, and it is convenient in production.

[0020] The concentration of water in solution (A) is preferably 3% by mass to 10% by mass, more preferably 6% by mass to 10% by mass, based on 100% by mass of solution (A). When the concentration of water in solution (A) is 3% by mass or more, the solubility of silicic acid produced by hydrolysis in the reaction solution is excellent. When the concentration of water in solution (A) is 10% by mass or less, the solubility of tetraalkoxysilane in the reaction solution is excellent.

[0021] The concentration of the alkali catalyst in solution (A) is preferably 0.5% by mass to 2.0% by mass, more preferably 0.6% by mass to 1.5% by mass, based on 100% by mass of solution (A). When the concentration of the alkali catalyst in solution (A) is 0.5% by mass or more, aggregation of silica particles is suppressed, and the dispersion stability of silica particles in the dispersion liquid is excellent. In addition, when the concentration of the alkali catalyst in solution (A) is 2.0% by mass or less, the reaction does not proceed excessively fast, and the reaction controllability is excellent.

[0022] The concentration of the solvent other than water in the solution (A) is preferably the balance of the alkali catalyst and water.

[0023] The solution (B) contains a tetraalkoxysilane. Examples of the tetraalkoxysilane in the solution (B) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. These tetraalkoxysilanes may be used alone or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, because they undergo a fast hydrolysis reaction, are less likely to leave unreacted substances, are highly productive, and can easily produce a stable silica sol.

[0024] The solution (B) preferably contains a solvent since this provides excellent solubility of the tetraalkoxysilane in the reaction solution. Examples of the solvent in the solution (B) include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used alone or in combination of two or more. Among these solvents, alcohol is preferred, more preferably methanol or ethanol, and even more preferably methanol, because the solvent used in the hydrolysis reaction and the solvent by-produced in the condensation reaction are the same, and the convenience in production is excellent.

[0025] The concentration of tetraalkoxysilane in solution (B) is preferably 60% by mass to 95% by mass, more preferably 70% by mass to 90% by mass, based on 100% by mass of solution (B). When the concentration of tetraalkoxysilane in solution (B) is 70% by mass or more, the amount of solvent used can be reduced, and the productivity of silica particles is excellent. In addition, when the concentration of tetraalkoxysilane in solution (B) is 90% by mass or less, the solubility of tetraalkoxysilane in the reaction solution is excellent.

[0026] The concentration of the solvent in solution (B) is preferably 5% by mass to 40% by mass, more preferably 10% by mass to 30% by mass, based on 100% by mass of solution (B). When the concentration of the solvent in solution (B) is 5% by mass or more, the solubility of tetraalkoxysilane in the reaction solution is excellent. In addition, when the concentration of the solvent in solution (B) is 40% by mass or less, the amount of the solvent used can be reduced, and the productivity of silica particles is excellent.

[0027] The addition rate of solution (B) is preferably 50g silica / hour / kg solution to 150g silica / hour / kg solution, more preferably 70g silica / hour / kg solution to 130g silica / hour / kg solution. When the addition rate of solution (B) is 50g silica / hour / kg solution or more, the reaction time is shortened and the productivity is excellent. In addition, when the addition rate of solution (B) is 150g silica / hour / kg solution or less, the solubility of tetraalkoxysilane in the reaction solution is excellent. Silica / hour / kg solution refers to the mass of tetraalkoxysilane added per hour to 1 kg of solution (A), converted into the mass of silica.

[0028] The solution (C) preferably contains water, since this can promote the hydrolysis reaction of the tetraalkoxysilane.

[0029] The solution (C) preferably contains an alkali catalyst, since this can increase the reaction rates of the hydrolysis reaction and condensation reaction of the tetraalkoxysilane. Examples of the alkali catalyst in the solution (C) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, is easy to control the particle shape, can suppress the inclusion of metal impurities, is highly volatile, and is easy to remove after the hydrolysis reaction and the condensation reaction.

[0030] The concentration of water in solution (C) is preferably 94% by mass to 99% by mass, more preferably 95% by mass to 98% by mass, based on 100% by mass of solution (C). When the concentration of water in solution (C) is 94% by mass or more, the solubility of silicic acid produced by hydrolysis in the reaction solution is excellent. In addition, when the concentration of water in solution (C) is 99% by mass or less, the solubility of tetraalkoxysilane in the reaction solution is excellent.

[0031] The concentration of the alkali catalyst in solution (C) is preferably 1% by mass to 6% by mass, more preferably 2% by mass to 5% by mass, based on 100% by mass of solution (C). When the concentration of the alkali catalyst in solution (C) is 1% by mass or more, aggregation of silica particles is suppressed, and the dispersion stability of silica particles in the dispersion is excellent. When the concentration of the alkali catalyst in solution (C) is 6% by mass or less, the reaction does not proceed excessively fast, and the reaction controllability is excellent.

[0032] The addition rate of solution (C) is preferably 2 g alkaline catalyst / hour / kg solution to 5 g alkaline catalyst / hour / kg solution, and more preferably 3 g alkaline catalyst / hour / kg solution to 4 g alkaline catalyst / hour / kg solution. When the addition rate of solution (C) is 2 g alkaline catalyst / hour / kg solution or more, the aggregation of silica particles is suppressed, and the dispersion stability of silica particles in the dispersion is excellent. When the addition rate of solution (C) is 5 g alkaline catalyst / hour / kg or less, the reaction does not proceed too quickly, and the reaction controllability is excellent. The term "alkali catalyst / hour / kg solution" refers to the mass of alkali catalyst added per hour per 1 kg of solution (A).

[0033] The reaction temperature of the hydrolysis reaction and the condensation reaction is preferably 20° C. to 50° C., more preferably 25° C. to 45° C. When the reaction temperature is 20° C. or higher, the reaction does not proceed too slowly, and controllability is excellent. On the other hand, when the reaction temperature is 50° C. or lower, a good balance between the hydrolysis reaction rate and the condensation reaction rate is obtained.

[0034] The concentration of water in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction is preferably 3% by mass to 20% by mass because this provides excellent solubility of tetraalkoxysilane in the reaction solution, and is more preferably 5% by mass to 18% by mass, and even more preferably 7% by mass to 15% by mass, because this provides excellent solubility of silicic acid produced by the hydrolysis reaction in the reaction solution and can further suppress the generation of fine particles.

[0035] The concentration of the alkali catalyst in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction is preferably 0.5% by mass to 2.0% by mass, more preferably 0.6% by mass to 1.5% by mass. When the concentration of the alkali catalyst in the reaction system is 0.5% by mass or more, the aggregation of the silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion liquid is excellent. In addition, when the concentration of the alkali catalyst in the reaction system is 2.0% by mass or less, the reaction does not proceed too quickly, and the reaction controllability is excellent.

[0036] The concentration of the alkali catalyst in the reaction system refers to the total amount of the alkali catalyst in the total amount of substances other than tetraalkoxysilane and silica in the reaction system in the hydrolysis reaction and condensation reaction. In other words, the concentration of the alkali catalyst in the reaction system is the total amount of the alkali catalyst in the total amount of solution (A) at the start of the reaction, and during the reaction is the total amount of the alkali catalyst in the total amount of substances in the reaction system excluding tetraalkoxysilane and silica produced by the reaction (water in the reaction system, alkali catalyst, solvent, and substances such as alcohol produced by the reaction).

[0037] (Process (1)) Since the method for producing silica particles of the present invention can remove unnecessary components and add necessary components, it is preferable that the method further includes the following step (1). Step (1): A step of concentrating the obtained dispersion liquid of silica particles and adding a dispersion medium.

[0038] Examples of the dispersion medium include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These dispersion media may be used alone or in combination of two or more. Among these dispersion media, water and alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.

[0039] (Process (2)) The method for producing silica particles of the present invention preferably further includes the following step (2) since the condensation degree of the silica particles can be increased. Step (2): A step of subjecting the dispersion liquid of silica particles obtained in step (1) to a pressure and heat treatment.

[0040] The pressure of the pressurized heat treatment is preferably 0.10 MPa to 2.3 MPa, more preferably 0.14 MPa to 1.0 MPa. When the pressure of the pressurized heat treatment is 0.10 MPa or more, the degree of condensation of the silica particles can be increased. When the pressure of the pressurized heat treatment is 2.3 MPa or less, the silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent. Pressurization can be achieved by heating the silica particle dispersion in a sealed state to above the boiling point of the dispersion medium. When the silica particle aqueous dispersion is heated to 100°C or higher in a sealed state, the pressure becomes the saturated water vapor pressure at that temperature.

[0041] The temperature of the pressure and heat treatment is preferably 100° C. to 220° C., and more preferably 110° C. to 180° C. When the temperature of the pressure and heat treatment is 100° C. or higher, the degree of condensation of the silica particles can be increased. When the temperature of the pressure and heat treatment is 220° C. or lower, silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.

[0042] The time of the pressurized heat treatment is preferably 0.25 hours to 10 hours, and more preferably 0.5 hours to 8 hours. When the time of the pressurized heat treatment is 0.25 hours or more, the degree of condensation of the silica particles can be increased. When the time of the pressurized heat treatment is 10 hours or less, the silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.

[0043] The pressurized heat treatment is preferably carried out in an aqueous dispersion because it can increase the degree of condensation of the silica particles without significantly changing the average primary particle size, the average secondary particle size, the cv value, or the association ratio.

[0044] The pH when the pressure heat treatment is carried out in the aqueous dispersion is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH when the pressure heat treatment is carried out in the aqueous dispersion is 6.0 or more, gelation of the silica sol can be suppressed. When the pH when the pressure heat treatment is carried out in the aqueous dispersion is 8.0 or less, the degree of condensation of the silica particles can be increased without significantly changing the average primary particle size, average secondary particle size, cv value, and association ratio.

[0045] (Physical properties of silica particles) The average primary particle diameter of the silica particles is preferably 5 nm to 100 nm, more preferably 10 nm to 60 nm. When the average primary particle diameter of the silica particles is 5 nm or more, the storage stability of the silica sol is excellent. Furthermore, when the average primary particle diameter of the silica particles is 100 nm or less, the surface roughness and scratches of the polished object, such as a silicon wafer, can be reduced, and the sedimentation of the silica particles can be suppressed.

[0046] The average primary particle size of the silica particles is measured by the BET method. Specifically, the specific surface area of ​​the silica particles is measured using an automatic specific surface area measuring device, and the average primary particle size is calculated using the following formula (1). Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ··· (1)

[0047] The average primary particle size of the silica particles can be set within a desired range by known conditions and methods.

[0048] The average secondary particle diameter of the silica particles is preferably 10 nm to 200 nm, more preferably 20 nm to 100 nm. When the average secondary particle diameter of the silica particles is 10 nm or more, the removability of particles and the like during cleaning after polishing is excellent, and the storage stability of the silica sol is excellent. When the average secondary particle diameter of the silica particles is 200 nm or less, the surface roughness and scratches of the polished object, typically a silicon wafer, during polishing can be reduced, and the removability of particles and the like during cleaning after polishing can be excellent, and sedimentation of the silica particles can be suppressed.

[0049] The average secondary particle size of the silica particles is measured by a DLS method, specifically, using a dynamic light scattering particle size measuring device.

[0050] The average secondary particle size of the silica particles can be set within a desired range by known conditions and methods.

[0051] The cv value of the silica particles is preferably 10 to 50, more preferably 15 to 40, and even more preferably 20 to 35. When the cv value of the silica particles is 10 or more, the polishing rate for a polished object such as a silicon wafer is excellent, and the productivity of the silicon wafer is excellent. When the cv value of the silica particles is 50 or less, the surface roughness and scratches of a polished object such as a silicon wafer during polishing can be reduced, and the removal of particles and the like during cleaning after polishing is excellent.

[0052] The cv value of the silica particles is calculated using the following formula (2) by measuring the average secondary particle size of the silica particles using a dynamic light scattering particle size measuring device. cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100 (2)

[0053] The association ratio of the silica particles is preferably 1.0 to 4.0, more preferably 1.1 to 3.0. When the association ratio of the silica particles is 1.0 or more, the polishing rate for the polished object, typically a silicon wafer, is excellent, and the productivity of the silicon wafer is excellent. When the association ratio of the silica particles is 4.0 or less, the surface roughness and scratches of the polished object, typically a silicon wafer, during polishing can be reduced, and the aggregation of the silica particles can be suppressed.

[0054] The association ratio of the silica particles is calculated using the following formula (3) from the average primary particle diameter measured by the above-mentioned measurement method and the average secondary particle diameter measured by the above-mentioned measurement method. Association ratio = average secondary particle diameter / average primary particle diameter (3)

[0055] The surface silanol group density of silica particles is 0.1 / nm 2 ~10 pieces / nm 2 is preferable, and 0.5 particles / nm 2 ~7.5 pieces / nm 2 More preferably, 2.0 particles / nm 2 ~7.0 pieces / nm 2 More preferably, the surface silanol group density of the silica particles is 0.1 / nm 2 When the surface silanol group density of the silica particles is 10 / nm or more, the silica particles have a suitable surface repulsion, and the dispersion stability of the silica sol is excellent. 2 When the amount is equal to or less than this, the silica particles have an appropriate surface repulsion, and aggregation of the silica particles can be suppressed.

[0056] The surface silanol group density of the silica particles is measured by the Sears method, specifically, under the following conditions. Take a silica sol equivalent to 1.5 g of silica particles, add pure water to make the liquid volume 90 mL, add 0.1 mol / L hydrochloric acid aqueous solution until the pH becomes 3.6 in an environment of 25°C, add 30 g of sodium chloride, gradually add pure water to completely dissolve the sodium chloride, and finally add pure water until the total volume of the test liquid is 150 mL to obtain the test liquid. The obtained test liquid is placed in an automatic titrator, and 0.1 mol / L aqueous sodium hydroxide solution is added dropwise to measure the titer A (mL) of 0.1 mol / L aqueous sodium hydroxide solution required to change the pH from 4.0 to 9.0. The amount of 0.1 mol / L sodium hydroxide solution consumed per 1.5 g of silica particles, V (mL), required to change the pH from 4.0 to 9.0 was calculated using the following formula (4), and the surface silanol group density ρ (particles / nm 2 ) is calculated. V=(A×f×100×1.5) / (W×C) ··· (4) A: The amount (mL) of 0.1 mol / L sodium hydroxide solution required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles f: Potency of the 0.1 mol / L sodium hydroxide solution used C: Concentration of silica particles in silica sol (mass%) W: Amount of silica sol collected (g) ρ = (B × N A ) / (10 18 ×M×S BET ) ··· (5) B: The amount of sodium hydroxide (mol) required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles calculated from V N A : Avogadro's number (pieces / mol) M: Silica particle amount (1.5g) S BET : The specific surface area (m2) of silica particles measured when calculating the average primary particle size 2 / g)

[0057] The method for measuring and calculating the surface silanol group density of the silica particles was based on "GW Ears, Jr., Analytical Chemistry, Vol. 28, No. 12, pp. 1981-1983 (1956)," "Haba Shinichi, Development of Abrasives for Semiconductor Integrated Circuit Processes, Doctoral Dissertation, Kochi University of Technology, pp. 39-45, March 2004," "Patent No. 5967118," and "Patent No. 6047395."

[0058] The surface silanol group density of the silica particles can be set within a desired range by adjusting the conditions for the hydrolysis reaction and condensation reaction of the alkoxysilane.

[0059] The metal impurity content of the silica particles is preferably 5 ppm or less, and more preferably 2 ppm or less.

[0060] When polishing silicon wafers for semiconductor devices, metallic impurities adhere to and contaminate the surface of the workpiece to be polished, adversely affecting the characteristics of the wafer and diffusing into the interior of the wafer, degrading its quality, resulting in a significant decrease in the performance of semiconductor devices manufactured from such wafers. In addition, when metal impurities are present on silica particles, coordination interactions occur between the acidic surface silanol groups and the metal impurities, changing the chemical properties (acidity, etc.) of the surface silanol groups and the three-dimensional environment of the silica particle surface (e.g. the ease of aggregation of silica particles), thereby affecting the polishing rate.

[0061] The metal impurity content of silica particles is measured by inductively coupled plasma mass spectrometry (ICP-MS). Specifically, a silica sol containing 0.4 g of silica particles is accurately weighed, sulfuric acid and hydrofluoric acid are added, and the mixture is heated, dissolved, and evaporated. Pure water is added to the remaining sulfuric acid droplets so that the total amount is exactly 10 g to create a test solution, which is then measured using an inductively coupled plasma mass spectrometry device. The target metals are sodium, potassium, iron, aluminum, calcium, magnesium, zinc, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel, and the sum of the contents of these metals is the metal impurity content.

[0062] The metal impurity content of the silica particles can be reduced to 5 ppm or less by obtaining the silica particles through hydrolysis and condensation reactions using alkoxysilane as the main raw material. In the method of deionizing alkali silicate such as water glass, sodium and other impurities derived from the raw material remain, making it extremely difficult to reduce the metal impurity content of silica particles to 5 ppm or less.

[0063] Examples of the shape of silica particles include spherical, chain-like, cocoon-like (also called lump-like or peanut-like), irregular shapes (for example, wart-like, bent, branched, etc.) etc. Among these silica particle shapes, when it is desired to reduce the surface roughness or scratches of a polished object, such as a silicon wafer, during polishing, a spherical shape is preferred, and when it is desired to increase the polishing rate of a polished object, such as a silicon wafer, an irregular shape is preferred.

[0064] Silica particles preferably have no pores because they have excellent mechanical strength and storage stability. The presence or absence of pores in the silica particles is confirmed by multipoint BET analysis using adsorption isotherms with nitrogen as the adsorption gas.

[0065] (Method of producing silica sol) The method for producing a silica sol of the present invention includes the method for producing silica particles of the present invention.

[0066] The silica sol may be produced by using the dispersion of silica particles obtained by the method for producing silica particles of the present invention as is, or by removing unnecessary components from the dispersion of silica particles obtained and adding necessary components.

[0067] The silica sol preferably contains silica particles and a dispersion medium. Examples of the dispersion medium in silica sol include water, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These dispersion mediums in silica sol may be used alone or in combination of two or more. Among these dispersion mediums in silica sol, water and alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.

[0068] The content of silica particles in the silica sol is preferably 3% by mass to 50% by mass, more preferably 4% by mass to 40% by mass, and even more preferably 5% by mass to 30% by mass, based on the total amount of the silica sol (100% by mass). When the content of silica particles in the silica sol is 3% by mass or more, the polishing rate for a polished object such as a silicon wafer is excellent. When the content of silica particles in the silica sol is 50% by mass or less, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent.

[0069] The content of the dispersion medium in the silica sol is preferably 50% by mass to 97% by mass, more preferably 60% by mass to 96% by mass, and even more preferably 70% by mass to 95% by mass, based on the total amount of the silica sol (100% by mass). When the content of the dispersion medium in the silica sol is 50% by mass or more, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent. In addition, when the content of the dispersion medium in the silica sol is 97% by mass or less, the polishing rate for the polished object, typically a silicon wafer, is excellent.

[0070] The content of silica particles and dispersion medium in the silica sol can be set within a desired range by removing unnecessary components from the components in the obtained dispersion of silica particles and adding necessary components.

[0071] In addition to the silica particles and the dispersion medium, the silica sol may contain other components such as an oxidizing agent, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and biocide, as necessary, within the range that does not impair the performance of the silica sol. In particular, it is preferable to include an antibacterial biocide in the silica sol, since this provides excellent storage stability of the silica sol.

[0072] Examples of antibacterial biocides include hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salt, ethylenediamine, glutaraldehyde, methyl p-hydroxybenzoate, sodium chlorite, etc. These antibacterial biocides may be used alone or in combination of two or more. Among these antibacterial biocides, hydrogen peroxide is preferred because it has excellent affinity with silica sol. Biocides also include those commonly referred to as bactericides.

[0073] The content of the antibacterial biocide in the silica sol is preferably 0.0001% by mass to 10% by mass, more preferably 0.001% by mass to 1% by mass, based on the total amount of the silica sol (100% by mass). When the content of the antibacterial biocide in the silica sol is 0.0001% by mass or more, the storage stability of the silica sol is excellent. When the content of the antibacterial biocide in the silica sol is 10% by mass or less, the inherent performance of the silica sol is not impaired.

[0074] The pH of the silica sol is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH of the silica sol is 6.0 or more, the dispersion stability is excellent and the aggregation of the silica particles can be suppressed. Also, when the pH of the silica sol is 8.0 or less, dissolution of the silica particles is prevented and the long-term storage stability is excellent. The pH of the silica sol can be adjusted to a desired range by adding a pH adjuster.

[0075] (polishing composition) The silica particles obtained by the method for producing silica particles of the present invention can be suitably used as a polishing composition. The polishing composition preferably contains the above-mentioned silica sol and a water-soluble polymer.

[0076] The water-soluble polymer enhances the wettability of the polishing composition to the object to be polished, such as a silicon wafer. The water-soluble polymer is preferably a polymer having a functional group with high water affinity, and the functional group with high water affinity has a high affinity with the surface silanol group of the silica particles, so that the silica particles and the water-soluble polymer are stably dispersed in the polishing composition in a closer vicinity. Therefore, when polishing the object to be polished, such as a silicon wafer, the effects of the silica particles and the water-soluble polymer function synergistically.

[0077] Examples of the water-soluble polymer include cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone, copolymers having a polyvinylpyrrolidone skeleton, and polymers having a polyoxyalkylene structure.

[0078] Examples of cellulose derivatives include hydroxyethyl cellulose, hydrolyzed hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose. An example of the copolymer having a polyvinylpyrrolidone skeleton is a graft copolymer of polyvinyl alcohol and polyvinylpyrrolidone. Examples of polymers having a polyoxyalkylene structure include polyoxyethylene, polyoxypropylene, and copolymers of ethylene oxide and propylene oxide.

[0079] These water-soluble polymers may be used alone or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethyl cellulose is more preferred, because they have high affinity with the surface silanol groups of silica particles and act synergistically to impart good hydrophilicity to the surface of the polished object.

[0080] The mass average molecular weight of the water-soluble polymer is preferably 1,000 to 3,000,000, more preferably 5,000 to 2,000,000, and even more preferably 10,000 to 1,000,000. When the mass average molecular weight of the water-soluble polymer is 1,000 or more, the hydrophilicity of the polishing composition is improved. When the mass average molecular weight of the water-soluble polymer is 3,000,000 or less, the affinity with silica sol is excellent, and the polishing rate for the object to be polished, typified by a silicon wafer, is excellent.

[0081] The mass average molecular weight of the water-soluble polymer is measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as the mobile phase, in terms of polyethylene oxide.

[0082] The content of the water-soluble polymer in the polishing composition is preferably 0.02% by mass to 10% by mass, more preferably 0.05% by mass to 5% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the water-soluble polymer in the polishing composition is 0.02% by mass or more, the hydrophilicity of the polishing composition is improved. Furthermore, when the content of the water-soluble polymer in the polishing composition is 10% by mass or less, the aggregation of silica particles during preparation of the polishing composition can be suppressed.

[0083] In addition to the silica sol and the water-soluble polymer, the polishing composition may contain other components, such as a basic compound, a polishing accelerator, a surfactant, a hydrophilic compound, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and biocide, as necessary, within the range that does not impair the performance of the polishing composition. In particular, it is preferable to include a basic compound in the polishing composition, since it is possible to perform chemical polishing (chemical etching) by applying a chemical action to the surface of an object to be polished, such as a silicon wafer, and because a synergistic effect with the surface silanol groups of the silica particles can improve the polishing speed of an object to be polished, such as a silicon wafer.

[0084] Examples of the basic compound include organic basic compounds, alkali metal hydroxides, alkali metal hydrogen carbonates, alkali metal carbonates, and ammonia. These basic compounds may be used alone or in combination of two or more. Among these basic compounds, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium hydrogen carbonate, and ammonium carbonate are preferred because they are highly soluble in water and have excellent affinity with silica particles and water-soluble polymers, and ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, with ammonia being even more preferred.

[0085] The content of the basic compound in the polishing composition is preferably 0.001% by mass to 5% by mass, more preferably 0.01% by mass to 3% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the basic compound in the polishing composition is 0.001% by mass or more, the polishing speed of the object to be polished, such as a silicon wafer, can be improved. In addition, when the content of the basic compound in the polishing composition is 5% by mass or less, the stability of the polishing composition is excellent.

[0086] The pH of the polishing composition is preferably 8.0 to 12.0, more preferably 9.0 to 11.0. When the pH of the polishing composition is 8.0 or more, the aggregation of silica particles in the polishing composition can be suppressed, and the dispersion stability of the polishing composition is excellent. When the pH of the polishing composition is 12.0 or less, the dissolution of silica particles can be suppressed, and the stability of the polishing composition is excellent. The pH of the polishing composition can be adjusted to a desired range by adding a pH adjuster.

[0087] The polishing composition can be obtained by mixing the silica sol obtained by the silica sol manufacturing method of the present invention, a water-soluble polymer, and, as necessary, other components. However, taking into consideration storage and transportation, the composition may be prepared at a high concentration and then diluted with water or the like immediately before polishing.

[0088] (polishing method) The polishing method of the present invention is a method of polishing using a polishing composition containing the silica sol obtained by the method for producing a silica sol of the present invention. As the polishing composition, it is preferable to use the polishing composition described above. A specific example of the polishing method is a method in which the surface of a silicon wafer is pressed against a polishing pad, the polishing composition of the present invention is dropped onto the polishing pad, and the surface of the silicon wafer is polished.

[0089] (Method of manufacturing semiconductor wafers) The method for producing a semiconductor wafer of the present invention includes the polishing method of the present invention, and the specific polishing method is as described above. Examples of semiconductor wafers include silicon wafers and compound semiconductor wafers.

[0090] (Method of manufacturing semiconductor devices) The method for producing a semiconductor device of the present invention includes the polishing method of the present invention, and the specific polishing method is as described above.

[0091] (Application) The silica particles obtained by the method for producing silica particles of the present invention and the silica sol obtained by the method for producing a silica sol of the present invention can be suitably used for polishing purposes, such as polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the planarization process when producing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, and the like, and among these, they can be particularly suitably used for polishing silicon wafers and chemical mechanical polishing. EXAMPLES

[0092] The present invention will be described in more detail below using examples. However, the present invention is not limited to the description of the following examples as long as it does not deviate from the gist of the present invention.

[0093] (Measurement of average primary particle size) The dispersions of silica particles obtained in the examples and comparative examples were dried at 150°C, and the specific surface area of ​​the silica particles was measured using an automatic specific surface area measuring device "BELSORP-MR1" (model name, Microtrack BEL Co., Ltd.). The density was calculated to be 2.2 g / cm using the following formula (1). 3 The average primary particle size was calculated. Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ··· (1)

[0094] (Measurement of average secondary particle size and cv value) The average secondary particle diameter of the silica particles in the dispersions of silica particles obtained in the examples and comparative examples was measured using a dynamic light scattering particle size measurement device "Zetersizer Nano ZS" (model name, manufactured by Malvern Instruments), and the cv value was calculated using the following formula (2). cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100 (2)

[0095] (Calculation of association ratio) The association ratio was calculated from the measured average primary particle size and average secondary particle size using the following formula (3). Association ratio = average secondary particle diameter / average primary particle diameter (3)

[0096] (Measurement of surface silanol group density) Of the dispersions of silica particles obtained in the Examples and Comparative Examples, an amount equivalent to 1.5 g of silica particles was placed in a 200 mL tall beaker, and purified water was added to make the liquid volume 90 mL. In an environment of 25°C, a pH electrode was inserted into the tall beaker, and the test liquid was stirred for 5 minutes with a magnetic stirrer. With stirring continued with the magnetic stirrer, 0.1 mol / L aqueous hydrochloric acid solution was added until the pH reached 3.6. The pH electrode was removed from the tall beaker, and with stirring continued with the magnetic stirrer, 30 g of sodium chloride was added, and pure water was gradually added until the sodium chloride was completely dissolved, and finally pure water was added until the total volume of the test liquid was 150 mL, and the test liquid was stirred for 5 minutes with a magnetic stirrer to obtain a test liquid. The tall beaker containing the obtained test solution was placed in an automatic titration device "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.), and the pH electrode and burette included with the device were inserted into the tall beaker. While stirring the test solution with a magnetic stirrer, 0.1 mol / L aqueous sodium hydroxide solution was dropped through the burette, and the titration amount A (mL) of 0.1 mol / L aqueous sodium hydroxide solution required to change the pH from 4.0 to 9.0 was measured. The amount of 0.1 mol / L sodium hydroxide solution consumed per 1.5 g of silica particles, V (mL), required to change the pH from 4.0 to 9.0 was calculated using the following formula (4), and the surface silanol group density ρ (particles / nm 2 ) was calculated. V=(A×f×100×1.5) / (W×C) ··· (4) A: The amount (mL) of 0.1 mol / L sodium hydroxide solution required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles f: Potency of the 0.1 mol / L sodium hydroxide solution used C: Concentration of silica particles in silica sol (mass%) W: Amount of silica sol collected (g) ρ = (B × N A ) / (10 18 ×M×S BET ) ··· (5) B: The amount of sodium hydroxide (mol) required to change the pH from 4.0 to 9.0 per 1.5 g of silica particles calculated from V N A: Avogadro's number (pieces / mol) M: Silica particle amount (1.5g) S BET : The specific surface area (m2) of silica particles measured when calculating the average primary particle size 2 / g)

[0097] (Measurement of fine particles) The dispersion of silica particles obtained in the examples and comparative examples was diluted 5000 times with ultrapure water, and 5 μL of the diluted dispersion of silica particles was dropped onto a silicon substrate and dried. Next, a field emission scanning electron microscope (model name "S-5200 type", Hitachi High-Technologies Corporation, FE-SEM) was used to irradiate the silicon substrate with an electron beam at an accelerating voltage of 5 kV, and a secondary electron image observed at a magnification of 50,000 times was taken. The photograph was imported into an image analysis type particle size distribution measurement software (software name "Mac-View Ver.4", Mountec Co., Ltd.), and the Heywood diameter and area of ​​all silica particles (80 to 120 particles) contained in the same field of view were measured. Particles with a Heywood diameter of less than 30 nm were defined as fine particles, and the ratio (area %) of the area of ​​fine particles to the total area of ​​all particles was calculated.

[0098] [Example 1] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and a solution (C-1) of 27.4 parts by mass of pure water and 4.5 parts by mass of 29% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 3.8 parts by mass of pure water, 105.1 parts by mass of methanol, and 4.7 parts by mass of 29% by mass of ammonia water, respectively, over 208 minutes. During the dropwise addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 26°C. After the dropwise addition, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 26°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0099] [Example 2] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and a solution (C-1) of 28.1 parts by mass of pure water and 4.6 parts by mass of 29% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 4.5 parts by mass of pure water, 103.8 parts by mass of methanol, and 4.7 parts by mass of 29% by mass of ammonia water, respectively, over 210 minutes. During the dropwise addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 29°C. After the dropwise addition, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 29°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0100] [Example 3] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and a solution (C-1) of 28.7 parts by mass of pure water and 4.6 parts by mass of 29% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 5.1 parts by mass of pure water, 102.4 parts by mass of methanol, and 4.6 parts by mass of 29% by mass of ammonia water, respectively, over 211 minutes. During the dropwise addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 31°C. After the dropwise addition, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 31°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0101] [Example 4] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.7 parts by mass of methanol, and a solution (C-1) of 31.7 parts by mass of pure water and 4.7 parts by mass of 29% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 7.7 parts by mass of pure water, 96.8 parts by mass of methanol, and 4.5 parts by mass of 29% by mass of ammonia water over 217 minutes. During the dropwise addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 36°C. After the dropwise addition, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 36°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0102] [Example 5] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and a solution (C-1) of 33.1 parts by mass of pure water and 13.8 parts by mass of 10% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 7.5 parts by mass of pure water, 80.3 parts by mass of methanol, and 10.8 parts by mass of 10% by mass of ammonia water over 240 minutes. During the drop, the reaction solution was stirred while maintaining the temperature of the reaction solution at 36°C. After the drop, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 36°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0103] [Comparative Example 1] A solution (B-1) of 100 parts by mass of tetramethoxysilane and 17.7 parts by mass of methanol, and a solution (C-1) of 26.1 parts by mass of pure water and 7.9 parts by mass of 10% by mass of ammonia water were dropped at a constant speed into a solution (A-1) of 8.5 parts by mass of pure water, 90.8 parts by mass of methanol, and 12.3 parts by mass of 10% by mass of ammonia water over 212 minutes. During the dropwise addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 36°C. After the dropwise addition, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 36°C. The reaction solution was concentrated, and the methanol was replaced with water. This was filtered to obtain an aqueous dispersion of silica particles. The evaluation results of the obtained silica particles are shown in Table 1.

[0104] [Table 1]

[0105] As can be seen from Table 1, the methods for producing silica particles in Examples 1 to 5 were able to suppress the generation of fine particles, compared to the method for producing silica particles in Comparative Example 1. This is believed to be because the solubility of tetraalkoxysilane and silicic acid produced by hydrolysis reaction in the reaction solution was maintained by reducing the change in water concentration in the reaction system from the start of the reaction to the end of the reaction. [Industrial Applicability]

[0106] The silica particles obtained by the method for producing silica particles of the present invention and the silica sol obtained by the method for producing a silica sol of the present invention can be suitably used for polishing purposes, such as polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the planarization process when producing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, and the like, and among these, they can be particularly suitably used for polishing silicon wafers and chemical mechanical polishing.

Claims

1. A method for producing silica particles, comprising adding a solution (B) containing a tetraalkoxysilane and a solution (C) containing water to a solution (A) containing water, and subjecting the tetraalkoxysilane to hydrolysis and condensation reactions, wherein the concentration of the tetraalkoxysilane in solution (B) is 95 mass% or less, and the change in water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to no more than 3 mass% is kept within the range of 3 mass%, and the method comprises the following step (1): Step (1): A step of concentrating the obtained dispersion liquid of silica particles and adding a dispersion medium.

2. The method for producing silica particles according to claim 1, wherein the reaction temperature of the hydrolysis reaction and the condensation reaction is 20°C to 50°C.

3. The method for producing silica particles according to claim 1 or 2, wherein the concentration of water in the reaction system is kept at 20 mass% or less from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction.

4. The method for producing silica particles according to any one of claims 1 to 3, further comprising the following step (2): Step (2): A step of subjecting the dispersion of silica particles obtained in step (1) to a pressure and heat treatment.

5. A method for producing a silica sol, comprising the method for producing silica particles according to any one of claims 1 to 4.

6. The method for producing a silica sol according to claim 5, wherein the concentration of silica particles in the silica sol is 3% by mass to 50% by mass.

7. A polishing method, comprising polishing with a polishing composition containing the silica sol obtained by the method for producing a silica sol according to claim 5 or 6.

8. A method for producing a semiconductor wafer, comprising the polishing method according to claim 7.

9. A method for manufacturing a semiconductor device, comprising the polishing method according to claim 7.

Citation Information

Patent Citations

  • Method for preparing styrene grafted silicon dioxide superhydrophobic thin film

    CN102140179A

  • Silica sol and manufacturing method therefor

    JP2005060217A

  • Electrostatic image-developing toner and electric charge-controlling particle for external addition

    JP2011185998A

  • Method for producing associated silica

    JP2013163622A

  • Silica powder and positively-charged toner

    JP2017039618A

Cited By

  • Method for producing aqueous-dispersible colloidal silica

    JP2026113418A